Interaction of ultrashort laser pulses with metal nanotips: a model system for strong-field phenomena - Krüger, Michael; Schenk, Markus; Hommelhoff, Peter; Wachter, Georg; Lemell, Christoph; Burgdoerfer, Joachim (New Journal of Physics, 2012)
We discuss the interaction of ultrashort near-infrared laser pulses with sharp metal tips at moderate nominal intensities (I 0 ∼ 10 11W cm -2). As external electric fields are strongly enhanced at such tips (enhancement factor ∼10) our system turns out to be an ideal miniature laboratory to investigate strong-field effects at solid surfaces. We analyse the electron-energy spectra as a function of the strength of the laser field and the static extraction field and present an intuitive model for their interpretation. The size of the effective field acting on the metal electrons can be determined from the electron spectra. The latter are also reproduced by time-dependent density functional theory (TDDFT) simulations. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
UnivIS-Import:2015-04-14:Pub.2012.nat.dphy.IAP.exphys.intera